Fish Farmers' Perceptions of the Role of Fisheries Extension Workers in Developing Aquaculture Businesses in Loa Kulu - Baiq Sulistyo Rini; Helminuddin Helminuddin; Fitriyana Fitriyana (International Journal of Information Engineering and Science, 2025)
Fisheries extension services play a strategic role in strengthening the capacity of fish farmers and accelerating the development of sustainable aquaculture businesses. The effectiveness of extension activities is strongly influenced by how fish farmers perceive the roles performed by fisheries extension workers. This study aims to analyze the level of fish farmers’ perceptions of the role of fisheries extension workers in developing aquaculture businesses in Loa Kulu District, Kutai Kartanegara Regency. In addition, this research examines the characteristics of fish farmers and analyzes the relationship between internal and external factors and the level of perception toward extension roles. This study employed a descriptive and correlational research design using both qualitative and quantitative approaches. A total of 42 respondents were selected from 719 fish farmers using the Slovin formula with a 15% margin of error and proportionate stratified random sampling across 10 villages. Data were collected through structured questionnaires using a Likert scale and analyzed using descriptive statistics and Spearman's rank correlation analysis. The results indicate that the overall perception of fish farmers toward the roles of fisheries extension workers—namely as educators, facilitators, motivators, innovators, advocates, organizers, and evaluators—falls within the high category. Among these roles, the organizer and facilitator roles received the highest perception scores. Internal factors such as age, income, and land area showed significant correlations with certain extension roles, particularly the roles of educator, motivator, and evaluator. External factors, including interaction with extension workers, interaction with traders, availability of market information, and access to aquaculture science and technology, were also significantly correlated with perception levels. These findings suggest that strengthening both socio-economic conditions and access to information and technology can enhance positive perceptions of extension services, ultimately contributing to more effective aquaculture development programs. The study highlights the importance of optimizing extension performance to sustain fish farmers’ productivity and welfare improvement.